Pengaruh partisipasi penyusunan anggaran, kejelasan sasaran anggaran, evaluasi anggaran, akuntabilitas publik, dan transparansi kebijakan publik terhadap kinerja manajerial satuan kerja perangkat daerah (studi empiris pada satuan kerja perangkat daerah pr - Amie Dhiza; Rasuli '; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The objective of the study is to examine empirically the effect of budget participation, budget goal clarity, budget evaluation, public accountability, and transparency of public policy to managerial performance Riau Provincial government agencies. The population in this study is a local government agency in the Government of Riau Province, amounting to 39 agencies. The sampling technique used was judgment sampling. Respondents in this study is the Echelon II, III, and IV in each agency that is focused on leader of agency, leader of planning, leader of evaluation and reporting, subpart leader of planning, as well as the subpart leader of the evaluation and reporting numbering 195 people. The results of the study came to the conclusion that the participation of budget preparation, budget goal clarity, budget evaluation, accountability, transparency publik and significant influence public policy on managerial performance Riau provincial government agencies. The magnitude of the effect of independent variables on the dependent variable is equal to 60%.Keywords : Budget Participation, Budget Goal Clarity, Budget Evaluation, Public Accountability, Transparency Of Public Policy, Managerial Performance.